Poly(Lactic Acid) (PLA)/Acrylonitrile Butadiene Styrene (ABS) with Graphene Nanoplatelet (GNP) Nanocomposites - Mohd Bijarimi; Noor Shahadah; Azizan Ramli; Said Nurdin; Waleed Alhadadi; Muhammad Zakir Muzakkar; Jamiluddin Jaafar (Universitas Gadjah Mada, 2020)
A melt blending of poly(lactic acid) (PLA)/acrylonitrile-butadiene-styrene (ABS) with 30:70 PLA:ABS was prepared by a twin screw extruder with a die of 25 mm width and 0.5 mm thickness with various loadings of graphene (0–1.0 wt.%). The PLA/ABS blends were evaluated by mechanical, morphology, thermal and interaction of the components of the blend. Results show the incorporation of graphene nanoplatelet (GNP) improved the tensile and modulus properties. Nevertheless, it was observed that at higher GNP loadings i.e. 0.6–1.0 wt.%, both tensile and modulus properties showed a decreasing trend. It was also found that the thermal stability for the blend slightly improved when graphene presence in the blend.